2020
DOI: 10.30738/natural.v7i1.5901
|View full text |Cite
|
Sign up to set email alerts
|

Student facilitator and explaining dengan mind mapping: efek pada hasil dan minat belajar

Abstract: This is an open access article under the CC-BY-SA license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Previous research revealed that the Student Facilitating and Explaining (SFAE) learning model can improve learning outcomes of physics subjects in high schools and can also improve critical thinking skills (Harefa, 2021;Mustikasari et al, 2019). Previous research also explains that communication skills can be honed through habituation during learning (Iksan et al, 2012;Karwono & Mularsih, 2017;Poetri & Saifuddin, 2020). In the current research, there has not been much research on communication skills and learning outcomes in elementary school students.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous research revealed that the Student Facilitating and Explaining (SFAE) learning model can improve learning outcomes of physics subjects in high schools and can also improve critical thinking skills (Harefa, 2021;Mustikasari et al, 2019). Previous research also explains that communication skills can be honed through habituation during learning (Iksan et al, 2012;Karwono & Mularsih, 2017;Poetri & Saifuddin, 2020). In the current research, there has not been much research on communication skills and learning outcomes in elementary school students.…”
Section: Introductionmentioning
confidence: 88%
“…In previous studies, it was stated that SFAE were able to promote learning outcomes (Harefa, 2021;Karwono & Mularsih, 2017;Poetri & Saifuddin, 2020). Nonetheless, throughout this research, we will examine how SFAE model is able to refine the learning outcomes and communication skills needed in 21st century learning in elementary schools.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation